Nanodiamond-Induced Thrombocytopenia in Mice Involve P-Selectin-Dependent Nlrp3 Inflammasome-Mediated Platelet Aggregation, Pyroptosis and Apoptosis - Hung, Shih-Che; Ke, Lu-Chu; Lien, Te-Sheng; Huang, Hsuan-Shun; Sun, Der-Shan; Cheng, Chia-Liang; Chang, Hsin-Hou (Frontiers in Immunology, 2022)
Nanodiamond (ND) has been developed as a carrier to conduct various in vivo diagnostic and therapeutic uses. Safety is one of the major considerations, while the hemocompatibility of ND is not clearly addressed. Here we found that, compared to the other sizes of ND with relatively inert properties, treatments of 50 nm ND induced stronger platelet aggregation, platelet pyroptosis, apoptosis and thrombocytopenia in mice. Blockage treatments of soluble P-selectin, reactive oxygen species (ROS), and Nlrp3 inflammasome inhibitors markedly suppressed such adverse effects, suggesting ND-induced platelet activation and pyroptosis involves surface P-selectin-mediated enhancement of mitochondrial superoxide levels and Nlrp3 inflammasome activation. In addition, challenges of NDs induced less platelet pyroptosis and displayed less thrombocytopenia in P-selectin (Selp-/-), Nlrp3 (Nlrp3-/-) and caspase-1 (Casp1-/-) mutants, as compared to the wild type mice. Blockers of P-selectin, ROS, and Nlrp3 inflammasome pathways could be considered as antidotes for ND induced platelet activation and thrombocytopenia.